(untitled) - Lamb, Charles W. (Mason, OH, 2006)
The content is average, but the text is very cluttered with extraneous sidebar information, symbols, different colored headings, and purple "online" blocks on many pages. My biggest complaint is that one chapter is completely missing
Keywords: Marketing; Management